Durability design of concrete structures in severe environment [ - Gjorv, Odd E. (Taylor & Francis, 2009)
"Taking a probabilistic approach to the engineering design issues, this book tackles the challenge of controlling durability and service life of concrete structures in severe environments. Many durability problems are caused by poor quality control as well as special problems during concrete construction. You must firmly grasp the issue of construction quality and variability before you can successfully control durability." "International relevant with a practical focus, this is the essential guide for consulting and construction engineers involved in the design and execution of new concrete structures."--BOOK JACKET